Going to Extremes: An International Perspective on the Economic Status of the Untied States Aged - Timothy M. Smeeding; Barbara B. Torrey; Lee Rainwater (Luxembourg Income Study (LIS), 1993)
Focuses on the relative conditions of aged populations in eight LIS countries, finding extreme differences in well being among single women as compared to married couples in some countries. Policy suggestions are made to help those worst off while also preserving incentives for private saving and income support among the aged.
Keywords: 330